2021
DOI: 10.3390/membranes11060380
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on the Combination of Different Pre-Treatments with Nanofiltration for Efficiently Restraining Membrane Fouling While Providing High-Quality Drinking Water

Abstract: Nanofiltration (NF) is a promising post-treatment technology for providing high-quality drinking water. However, membrane fouling remains a challenge to long-term NF in providing high-quality drinking water. Herein, we found that coupling pre-treatments (sand filtration (SF) and ozone–biological activated carbon (O3-BAC)) and NF is a potent tactic against membrane fouling while achieving high-quality drinking water. The pilot results showed that using SF+O3-BAC pre-treated water as the feed water resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Compared with the quantitative analysis by UV 254 and DOC, the three-dimensional uorescence spectroscopy method is specialized in both the quantitative and qualitative analysis of organics, which presents high sensitivity and high efficiency without damage to the sample. 6,10,13,21,22,28 We selected samples in July as the target to analyze the constitution of organics in water, and the result is presented in Fig. 5.…”
Section: Constitution Of Organics Of the Watermentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with the quantitative analysis by UV 254 and DOC, the three-dimensional uorescence spectroscopy method is specialized in both the quantitative and qualitative analysis of organics, which presents high sensitivity and high efficiency without damage to the sample. 6,10,13,21,22,28 We selected samples in July as the target to analyze the constitution of organics in water, and the result is presented in Fig. 5.…”
Section: Constitution Of Organics Of the Watermentioning
confidence: 99%
“…Some reports also indicated they came from protein-like substances. 10,13,21,22,28 Fig. 6 shows the variations in the regional integral volume and its values represent the variations in the concentration of organics in an indirect way.…”
Section: Constitution Of Organics Of the Watermentioning
confidence: 99%
See 2 more Smart Citations
“…This study contributes to the optimization and enhancement of the pretreatment stage in the SWRO desalination process, and provides guidance for designing more-efficient and sustainable pretreatment schemes. pretreatments nor membrane technologies guarantee the comprehensive removal of DOM from the feedwater of RO systems [12][13][14]. Lin et al [15] showed that aluminum-based coagulants remove more than 60% of fulvic acid-like organics in HA/AOM mixtures while exhibiting minimal removal of aromatic protein-like substances.…”
Section: Introductionmentioning
confidence: 99%